Picoliter-Droplet Digital Polymerase Chain Reaction-Based Analysis of Cell-Free Plasma DNA to Assess EGFR Mutations in Lung Adenocarcinoma That Confer Resistance to Tyrosine-Kinase Inhibitors. (14th January 2016) - Seki, Yoshitaka; Fujiwara, Yutaka; Kohno, Takashi; Takai, Erina; Sunami, Kuniko; Goto, Yasushi; Horinouchi, Hidehito; Kanda, Shintaro; Nokihara, Hiroshi; Watanabe, Shun-ichi; Ichikawa, Hitoshi; Yamamoto, Noboru; et al.
Abstract: Purpose: The objective of this study was to evaluate the utility of analyzing cell-free plasma DNA (cfDNA) by picoliter-droplet digital polymerase chain reaction (ddPCR) to detect EGFR mutations that confer resistance to tyrosine-kinase inhibitors (TKIs) used for treatment of lung adenocarcinoma (LADC). Experimental design: Thirty-five LADC patients who received epidermal growth factor receptor (EGFR)-TKI therapy, including ten who received tumor rebiopsy after development of resistance, were subjected to picoliter-ddPCR-cfDNA analysis to determine the fraction of cfDNA with TKI-sensitive (L858R and inflame exon 19 deletions) and -resistant (i.e., T790M) mutations, as well as their concordance with mutation status in rebiopsied tumor tissues. Results: cfDNA samples from 15 (94%) of 16 patients who acquired resistance were positive for TKI-sensitive mutations. Also, 7 (44%) were positive for the T790M mutation, with fractions of T790M (+) cfDNA ranging from 7.4% to 97%. T790M positivity in cfDNA was consistent in eight of ten patients for whom rebiopsied tumor tissues were analyzed, whereas the remaining cases were negative in cfDNA and positive in rebiopsied tumors. Prior to EGFR-TKI therapy, cfDNAs from 9 (38%) and 0 of 24 patients were positive for TKI-sensitive and T790M mutations, respectively. Next-generation sequencing of cfDNA from one patient who exhibited innate resistance to TKI despite a high fraction of TKI-sensitive mutations and the absence of the T790M mutation in his cfDNA revealed the presence of the L747P mutation, a known driver of TKI resistance. Conclusion: Picoliter-ddPCR examination of cfDNA, supported by next-generation sequencing analysis, enables noninvasive assessment of EGFR mutations that confer resistance to TKIs. Abstract : Lung adenocarcinoma patients who received epidermal growth factor receptor (EGFR)-tyrosine-kinase inhibitor (TKI) therapy were subjected to picoliter-droplet digital polymerase chain reaction (ddPCR)-cell-free plasma DNA (cfDNA) analysis to determine the fraction of cfDNA with TKI-sensitive and -resistant mutations, as well as their concordance with mutation status in rebiopsied tumor tissues. Picoliter-ddPCR examination of cfDNA, supported by next-generation sequencing analysis, enables noninvasive assessment of EGFR mutations that confer resistance to TKIs.